1988
DOI: 10.1029/gb002i003p00253
|View full text |Cite
|
Sign up to set email alerts
|

Potential methane production and methane oxidation rates in peatland ecosystems of the Appalachian Mountains, United States

Abstract: Potential rates of methane production and carbon dioxide production were measured on 11 dates in 1986 in peat from six plant communities typical of moss‐dominated peatlands in the Appalachian Mountains. Annual methane production ranged from 2.7 to 17.5 mol m−2, and annual carbon dioxide production ranged from 30.6 to 79.0 mol m−2. The wide range in methane production values among the communities found within a single peatland indicates that obtaining one production value for a peatland may not be appropriate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 36 publications
3
62
1
Order By: Relevance
“…For example, depth-integrated CH, production of 647 pmol cm-2 min-' (Table 3) minus CH, release into the atmosphere of 80 pmol cme2 min-l suggests that 88% of the CH, produced is oxidized. Yavitt et al (1988) has shown that > 50% of the CH, produced by peats in a wide range of wetlands is oxidized before it can be released into the atmosphere. Collectively, these data indicate that impoundment scdimcnts produce more CH, than wetlands and that more of the CH, pro- duced in the impoundments finds its way into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…For example, depth-integrated CH, production of 647 pmol cm-2 min-' (Table 3) minus CH, release into the atmosphere of 80 pmol cme2 min-l suggests that 88% of the CH, produced is oxidized. Yavitt et al (1988) has shown that > 50% of the CH, produced by peats in a wide range of wetlands is oxidized before it can be released into the atmosphere. Collectively, these data indicate that impoundment scdimcnts produce more CH, than wetlands and that more of the CH, pro- duced in the impoundments finds its way into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…AOM as a sink for CH 4 has been alluded to in peat soils (Nedwell and Watson, 1995;Yavitt et al, 1988), but until recently no data had been presented. Rather, conceptual models of CH 4 cycling in peat-forming wetlands (Fig.…”
Section: Peatland Ecosystemsmentioning
confidence: 99%
“…In this research, the pmoA gene number of soil total methanotrophic bacteria, the numbers of type I and type II methanotrophic bacteria were not in significant correlation with PMOR, indicating that PMOR is not determined by the number of methanotrophic bacteria. PMPR is generally associated with the activity of soil methanotrophic bacteria (Yavitt et al, 1988). The research on the influence of different O 3 concentrations on the PMPR of winter wheat field soil indicated that the soil PMPR increased as at deeper depth without O 3 fumigation.…”
Section: The Influence Of O 3 Concentration Increase On Pmor and Pmprmentioning
confidence: 99%